2015
DOI: 10.1016/j.chroma.2015.07.094
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method for the chromatographic analysis of volatile organic compounds in exhaled breath of tobacco cigarette and electronic cigarette smokers

Abstract: A method for the rapid analysis of volatile organic compounds (VOCs) in smoke from tobacco and electronic cigarettes and in exhaled breath of users of these smoking systems has been developed. Both disposable and rechargeable e-cigarettes were considered. Smoke or breath were collected in Bio-VOCs. VOCs were then desorbed in Tenax cartridges which were subsequently analyzed by thermal desorption coupled to gas chromatography-mass spectrometry. The method provides consistent results when comparing the VOC compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…In this research, 11 compounds were found to be consistent with literature reporting exhaled breath profiles of smokers. Those compounds of the current study identified in smokers are as follows: propanoic acid [91], propylene glycol [33], α-pinene [91,92], β-pinene [91,92], octanal [91], eucalyptol [91,92], undecane [91,92], menthone [92], nicotine [8,33,35,54], pentadecane [9] and butylated hydroxytoluene [9]. In this research, 17 compounds were reported in literature as being consistent with exhaled breath profiles of both smokers and nonsmokers.…”
Section: Smoker and Nonsmoker Breath Analysissupporting
confidence: 60%
See 4 more Smart Citations
“…In this research, 11 compounds were found to be consistent with literature reporting exhaled breath profiles of smokers. Those compounds of the current study identified in smokers are as follows: propanoic acid [91], propylene glycol [33], α-pinene [91,92], β-pinene [91,92], octanal [91], eucalyptol [91,92], undecane [91,92], menthone [92], nicotine [8,33,35,54], pentadecane [9] and butylated hydroxytoluene [9]. In this research, 17 compounds were reported in literature as being consistent with exhaled breath profiles of both smokers and nonsmokers.…”
Section: Smoker and Nonsmoker Breath Analysissupporting
confidence: 60%
“…Examples of sorbent materials used for pre-concentration of exhaled breath samples are activated carbon sorbents [8], SPME fibers [36,38,40,41] and Tenax® sorbent tubes [33,42] followed by analytical techniques such as GC/MS [8,9,35,40,41] or ion mobility spectrometry [42] analysis. During the early stages of exhaled breath analysis, researchers often collected breath into a reservoir and then pumped the sample through an activated carbon sorbent for solvent desorption extraction [8].…”
Section: Trappingmentioning
confidence: 99%
See 3 more Smart Citations